2021
DOI: 10.3390/agriculture11030274
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sustainability of Organic Livestock Farming in Sicily: A Case Study Using the FAO SAFA Framework

Abstract: Greenhouse gas (GHG) emissions and pollutants, soil erosion and groundwater pollution are some of the negative aspects blamed on livestock farming, so their level of sustainability needs to be assessed, taking into account the territory in which they operate. The research focuses on the assessment of sustainability performance in the four dimensions of good governance: environmental integrity, economic resilience and social well-being, considered by the ‘‘Sustainability Assessment of Food and Agriculture Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
0
10
0
8
Order By: Relevance
“…The study by [87] in the central Sicily Mountains showed that a growing economy would also require more resources to reduce environmental impacts, modernize animal shelters and use renewable energy sources to make them more sustainable. It illustrates how, on the one hand, the sustainability areas that are discussed in SAFA are interconnected, and, on the other, that there are many open pathways for Sicilian organic farms to improve their performance.…”
Section: Safamentioning
confidence: 99%
“…The study by [87] in the central Sicily Mountains showed that a growing economy would also require more resources to reduce environmental impacts, modernize animal shelters and use renewable energy sources to make them more sustainable. It illustrates how, on the one hand, the sustainability areas that are discussed in SAFA are interconnected, and, on the other, that there are many open pathways for Sicilian organic farms to improve their performance.…”
Section: Safamentioning
confidence: 99%
“…In Sicily, sustainability performance was studied under dimensions of good governance: environmental integrity, economic resilience and social well-being under the framework of the Sustainability Assessment of Food and Agricultural Systems" (SAFA) developed by FAO. It was implemented in ten agricultural systems, providing farmers with a tool that allows them to know the critical points on which they must intervene in search of sustainable development (9).…”
Section: Situation Contextmentioning
confidence: 99%
“…These problems can exert dramatic influences on the level of SH, causing a decrease in crop yields, decline in agricultural product quality, reduction in biodiversity, and even human health hazard. In view of the external attributes or environmental factors that limit the sustainability of SH, the indicators of SH hazards for farmland, including the degree of soil salinization, depth of the barrier layer, degree of soil erosion, white pollution, pesticide residues, irrigation water pollution, heavy metals pollution, atmospheric pollution, degree of surface rock exposure, crop pollution, gravel content, soil acidification, soil compaction, flood disasters, and soil alkalization, were selected in the present study [61][62][63][64][65].…”
Section: Selection Of Evaluation Indicatormentioning
confidence: 99%